2013
DOI: 10.1016/j.bbadis.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Green tea phenolics inhibit butyrate-induced differentiation of colon cancer cells by interacting with monocarboxylate transporter 1

Abstract: Diet has a significant impact on colorectal cancer and both dietary fiber and plant-derived compounds have been independently shown to be inversely related to colon cancer risk. Butyrate (NaB), one of the principal products of dietary fiber fermentation, induces differentiation of colon cancer cell lines by inhibiting histone deacetylases (HDACs). On the other hand, (−)-epicatechin (EC) and (−)-epigallocatechin gallate (EGCG), two abundant phenolic compounds of green tea, have been shown to exhibit antitumoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Two given compounds can act differently at different dose combinations. From our MTT assays we showed that at 2 mM NaB and 10 μM EGCG there was no additive or synergistic effect observed in HT-29 cells which was the same cell line chosen for the previous study [34]. Therefore, dose appears to be crucial in determining chemotherapeutic effects.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Two given compounds can act differently at different dose combinations. From our MTT assays we showed that at 2 mM NaB and 10 μM EGCG there was no additive or synergistic effect observed in HT-29 cells which was the same cell line chosen for the previous study [34]. Therefore, dose appears to be crucial in determining chemotherapeutic effects.…”
Section: Discussionmentioning
confidence: 88%
“…On the contrary, a study showed that EGCG interferes with butyrate-induced differentiation in colon cancer cells by preventing the cellular uptake of NaB [34]. However, in the study conducted, the dose chosen was based on the optimal values of the individual compounds and not on the combination of the compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is one of the leading causes of death in western countries (1), and the incidence is still increasing. Approximately 70% of patients with CRC are >65 years while the disease is rare under the age of 45 (2).…”
Section: Introductionmentioning
confidence: 99%
“…Treatments with HDAC inhibitors usually resulted in growth arrest, apoptosis and inhibition of angiogenesis in cancer cells (Marks and Xu ; Sánchez‐Tena et al . ), with the cancer cell apoptosis effect being due to a shift in the balance of pro‐ and anti‐apoptotic genes (Carew et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…HDAC inhibitors acting on classical HDACs have been classified into four subtypes based on their chemical structures: (1) aliphatic acids or short chain fatty acids; (2) hydroxamic acids; (3) benzamides; and (4) cyclic peptides (Hrabeta et al 2014). Treatments with HDAC inhibitors usually resulted in growth arrest, apoptosis and inhibition of angiogenesis in cancer cells (Marks and Xu 2009;Sánchez-Tena et al 2013), with the cancer cell apoptosis effect being due to a shift in the balance of pro-and anti-apoptotic genes (Carew et al 2008). Because of their low toxicity, HDAC inhibitors constitute a promising treatment for cancer, especially in combination with other chemotherapeutic agents (Carew et al 2008;Bots and Johnstone 2009;Ma et al 2009).…”
Section: Introductionmentioning
confidence: 99%